Sociopreneurship Business Incubator Design Based On Information Technology As an Innovative Solution for Enhancing Community Welfare - Vieqi Rakhma Wulan; Agus Hermanto (IJEBD International Journal Of Entrepreneurship And Business Development eISSN 2597-4785 pISSN 2597-4750)
Purpose: This research aimed is to design a sociopreneurship (Social Entrepreneurship) business incubator system by integrating the Information Technology Infrastructure Library (ITIL) features as a supporting tool in managing business incubator. With the sociopreneurship business incubator design is expected to help overcome social problems that occur in the community. Design/methodology/approach: This research is a qualitative research using the Human Centered Design (HCD) method. The stages in this HCD method are Hear, Create and Delivery. However, because the purpose of this study is to design, the stages that are passed are up to the Create stage. Findings: Based on the research, business incubators design were produced with 7 business fields, 5 service fields, 2 phases, namely co worker space and event space with details: 5 programs and activities in the co worker space phase and 2 programs and activities in the event space phase. Business incubator system also designed by integrating the Information Technology Infrastructure Library (ITIL) features as a supporting tool in managing business incubator. Research limitations/implications: This research is limited to the design so that the 3 stages of the HCD method are used only up to the second stage, namely the Create stage. Practical implications: In this research, it seeks to accommodate the community's needs for a business field so that services and programs of business incubator can be obtained that are in accordance with the needs of the community. This study also seeks to present a business incubator that is tailored to the needs of the community so that the community does not only have economic independence but can be mutually transmitted and sustainable with other communities (sociopreneurship) and by utilizing information technology. Originality/value: In this study the researchers collected, identified and interpreted the data that had been obtained. For this purpose, a literature review and approach to the HCD method are used through interview techniques by approaching the community and analyzing their needs in order to produce an analysis of results accordingly. Paper type: Research paper